2020
DOI: 10.1002/anie.202000838
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Redox‐Divergent Chiral Phosphoric Acid Catalyzed Quinone Diels–Alder Reactions

Abstract: An efficient enantioselective construction of tetrahydronaphthalene-1,4-diones as well as dihydronaphthalene-1,4-diols by a chiral phosphoric acid catalyzed quinone Diels-Alder reaction with dienecarbamates is reported. The nature of the protecting group on the diene is key to the success of achieving high enantioselectivity. The divergent "redox" selectivity is controlled by using an adequate amount of quinones. Reversible redox switching without erosion of enantioselectivity was possible from individual redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…As such, Bernardi et al reported the use of simple unsubstituted dienecarbamates [12] in Povarov reaction leading to the synthesis of 1,2,3,4-tetrahydroquinolines (Scheme 1b, right). [13] In continuation of our research program in catalytic asymmetric reactions with dienecarbamates, [14] we decided to explore their reactivities in connection with 2-benzothiazolimines. Indeed, these imines are versatile synthetic intermediates used for the syntheses of various heterocycles [15] and they have been embedded in direct catalytic asymmetric annulation strategies.…”
Section: Tetrahydropyridinesmentioning
confidence: 99%
“…As such, Bernardi et al reported the use of simple unsubstituted dienecarbamates [12] in Povarov reaction leading to the synthesis of 1,2,3,4-tetrahydroquinolines (Scheme 1b, right). [13] In continuation of our research program in catalytic asymmetric reactions with dienecarbamates, [14] we decided to explore their reactivities in connection with 2-benzothiazolimines. Indeed, these imines are versatile synthetic intermediates used for the syntheses of various heterocycles [15] and they have been embedded in direct catalytic asymmetric annulation strategies.…”
Section: Tetrahydropyridinesmentioning
confidence: 99%
“…Following our work on the asymmetric (3 + 2) cycloaddition between enecarbamates and quinones, 76 we found that thiodienecarbamates could effectively react with quinones in an enantioselective (4 + 2)-cycloaddition with (S)-SPINOL (S)-5b as chiral phosphoric acid catalyst. 77 Interestingly, a divergent synthesis of redox isomers, dihydronaphthalene-1,4-diols 75 and tetrahydronaphthalene-1,4-diones 76, 75b,78 was controlled by adequate amount of the quinones employed. The enantioselectivity was found to be highly dependent on the protecting group of the diene.…”
Section: Scheme 21mentioning
confidence: 99%
“…In general, binaphthyl is used to synthesize chiral phosphoric acid derivatives. These catalysts have been involved in several reactions including the Diels-Alder, Nazarov, Mukaiyama Aldol, Mannich, Henry, Morita-Baylis-Hillman reactions, and 1,3-dipolar cycloadditions [146][147][148][149][150][151][152][153][154].…”
Section: Phosphoric Acidmentioning
confidence: 99%